“THE DEVELOPMENT OF PUBLIC PREPAREDNESS IN THE HISTORY OF THE CIVIL DEFENSE SYSTEM” - Teshaboyev, Boburjon (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
This article analyzes the formation and development of the civil defense system in the Republic of Uzbekistan, focusing on its organizational, legal, and educational foundations for preparing the population for emergencies. It examines the introduction of the subject “Fundamentals of Life Safety” within the National Program for Personnel Training, the evolution of civil defense education programs, and their practical outcomes. The role of neighborhood assemblies (mahalla) and the Civil Defense Institute in enhancing public readiness is highlighted. The study also discusses current challenges, such as insufficient methodological support, lack of continuity in personnel training, and limited use of innovative approaches. Finally, the paper proposes practical measures for modernizing the system, implementing digital education technologies, and fostering a culture of safety.